Case Report: A New Geographic Area for the Presence of the Zoonotic Ocular Nematode, Onchocerca lupi in Romania - Deak, Georgiana; Toader, Serenela; Soare, Diana Gabriela; Ionică, Angela Monica; Taulescu, Marian; Mihalca, Andrei Daniel (Frontiers in Veterinary Science, 2022)
IIntroduction Onchocerca lupi is a zoonotic parasite of carnivores reported in countries from Europe, North America, Asia and Africa. In Romania, canine ocular onchocercosis was first reported in dogs in 2016 from Târgoviște (Dâmbovița County) and Onești (Bacău County) and more recently, it was detected in an adult stray dog exported to UK from an unspecified location in Romania. Methods A 4-years old male mongrel dog was referred to a private veterinary clinic in Năvodari (Constanța County), Romania due to ocular disorders. The dog was originally from a public dog shelter in Balș (Olt County) and transferred in June 2020 to a dog shelter in Medgidia (Constanța County). A cytological examination followed by surgical removal of the granuloma localized at the internal angle of the right eye, and molecular identification of the extracted nematode were done. Results The cytological examination confirmed a parasitic granuloma. Skin biopsy and PCR confirmed the infection with O. lupi. Two doses of moxidectin and imidacloprid were administered after the surgery. No relapse observed after a period of follo-up of 11 months. Conclusion Onchocerca lupi is present in dogs from Romania with its actual distribution remaining unknown.